2017
DOI: 10.1007/s00701-017-3105-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment and outcome of TSH-producing pituitary adenomas

Abstract: We argue that transsphenoidal surgery for TSHoma should be considered as the treatment of choice as remission following surgery is highly probable and postoperative hypopituitarism is very unlikely if patients are referred to centers with high pituitary surgery case loads.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
1
5
0
1
Order By: Relevance
“…Some authors have recently suggested that SSA may play a role in the treatment of TSHoma as primary therapy reducing the risk of post-operative hypopituitarism (24). In 4 case series including 131 patients, 21 subjects (16%) developed hypopituitarism between 4 months and 15 years after surgery (26,27,28,29). During a mean follow-up time of 12 (7-15) months, seven out of the eight analysed case reports treated with SSA in monotherapy had normalization of TSH secretion.…”
Section: Diagnosismentioning
confidence: 99%
“…Some authors have recently suggested that SSA may play a role in the treatment of TSHoma as primary therapy reducing the risk of post-operative hypopituitarism (24). In 4 case series including 131 patients, 21 subjects (16%) developed hypopituitarism between 4 months and 15 years after surgery (26,27,28,29). During a mean follow-up time of 12 (7-15) months, seven out of the eight analysed case reports treated with SSA in monotherapy had normalization of TSH secretion.…”
Section: Diagnosismentioning
confidence: 99%
“…[18] The rate of postoperative biochemical remission is 70% to 90%. [7,18,19] In the past, a diagnosis of TSHoma was often delayed, resulting in an invasive macroadenoma, which complicates the surgical procedure. The preoperative MRI findings in our patient showed a microadenoma without mass effect in the sellar region, suggesting an early diagnosis in this case, significantly reducing the difficulty of the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a relatively good outcome of the surgical removal of TSH-PA has been reported. Yamada et al 20) reported a remission rate of 84% for surgery for TSH-PA, whereas Rotermund et al 16) also reported a remission rate of surgery alone for TSH-PA of 91.7% in their case series. In our series, the remission rate of TSH-PA after surgical treatment alone was 92.3%.…”
Section: Discussionmentioning
confidence: 93%